Mixed-Signal Approximate Computation: A Neural Predictor Case Study - St. Amant, Renee; Jiménez, Daniel A.; Burger, Doug (IEEE Micro, 2009)
As transistors shrink and processors trend toward low power, maintaining precise digital behavior grows more expensive. Replacing digital units with analog equivalents sometimes allows similar computation to be performed at higher speed using less power. As a case study in mixed-signal approximate computation, the authors describe an enhanced neural prediction algorithm and its efficient analog implementation.